The Implementation of Disaster Resilient Tourism Development Policy in the Padang City - Ahmad, Taufani; Putera, Roni Ekha; Koeswara, Hendri (Universitas Muhammadiyah Gorontalo, 2024)
The purpose of this research is to describe and analyze the implementation of the disaster-resilient tourism development policy in the City of Padang. Data collection techniques include observation, interviews, and documentation. The data analysis techniques employed are data reduction, data presentation, conclusion drawing, and verification. The research results conclude that, overall, disaster-resilient tourism development in the City of Padang has been implemented but is not yet optimal. The absence of regulations and derivative documents that can serve as guidelines for stakeholders and the community has led to hesitation and passivity in executing the policy. In terms of resources, the limited funding available to the subdistricts and districts involved has caused the policy implementation to stagnate in these areas. Furthermore, regarding communication and coordination between organizations, although socialization efforts have been made, the subdistricts and districts involved still lack clarity on the standards and benchmarks of the policy. Poor communication and coordination between the city-level policy implementers and the district- and subdistrict-level stakeholders have resulted in relationships that do not align with the initial plans. Regarding the attitudes of policy implementers, it was found that stakeholders responded positively; however, this positive response was not accompanied by a commitment from stakeholders at the district and subdistrict levels. Finally, the social, economic, and political environments, which are not conducive, have a direct impact on the performance of the policy that has been implemented.